Ecology and Current Distribution of Three Habitat-Specialized Land Snail Species of the Genus Vertigo (Gastropoda: Eupulmonata) in Europe - Coufal, Radovan; Horsáková, Veronika; Peterka, Tomáš; Ryelandt, Julien; Skujienė, Grita; Horsák, Michal (Zoological studies, 2024)
Our understanding of species distribution and ecology is critical to properly assess their conservation status. Vertigo lilljeborgi, V. genesii, and V. geyeri have the centre of their current distribution in northern Europe, where their occurrence is relatively frequent. However, to the south their occurrence is fragmented and restricted to sites of late glacial/early Holocene origin. In the last ~30 years, there has been an increase in records, connected with the listing of the latter two species in Annex II of the EU Habitats Directive (94/43/EEC). However, there is no comprehensive publication documenting their pan-European distribution. Therefore, we assembled all available data from online databases, books, and scientific literature and combined them with our unpublished records to create distribution maps. The results show a more frequent occurrence in temperate Europe than previously known, especially for V. geyeri. Analyses performed on data from 327 ecologically potentially suitable sites, covering the entire distribution range of the species, have improved our knowledge of their ecology. Vertigo lilljeborgi and especially V. genesii are restricted to areas with lower summer and winter temperatures, and therefore, their further decline is expected in the face of rising temperatures due to climate change. The preference of V. geyeri for higher temperatures, in comparison to the latter two species, may explain its relatively frequent distribution in temperate Europe. Vertigo lilljeborgi favors base-poor sites, while V. genesii and V. geyeri prefer calciumrich sites, with the latter being the most calcicolous. Their need for a stable water regime and lowproductive sites, known from previous studies, was not conspicuous in our results, probably due to the selection of sites well within the species range. Despite the increase in record frequency, these species are still endangered, especially in temperate Europe. Their sites should therefore be strictly protected as sites of high biological diversity and conservation value. Because of their relict nature, these land snails should be considered umbrella species and indicators of well-preserved groundwater-dependent ecosystems in temperate Europe.
Keywords: IUCN Red List species; Vertigo geyeri; Climate change; Vertigo lilljeborgi; Vertigo genesii; Glacial relicts; EU Habitats Directive